Effects of tungsten doping on structure and photoluminescence of MoO3–x nanomaterials. (23rd July 2020) - Wang, B B; Zhong, X X; Shao, R W; Chen, Y A; Cvelbar, U; Ostrikov, K
Abstract: The challenge in molybdenum oxides intended for integration into electronic, optical, energy conversion, and other devices is tuning of their photoluminescence (PL) properties. Despite some initial studies on possibilities of tuning PL properties, this issue remains unresolved. For this reason, we explored the tailoring of PL properties of molybdenum oxide nanomaterials with a dopant through a robust synthesis by hot filament chemical vapour deposition. Here the MoO3– x nanomaterials are doped with tungsten in a low concentration, and the room temperature PL properties are studied. The obtained results highlight the interaction of Mo 5+ defects and oxygen vacancies, which are playing an essential role in the enhancement of green PL emission. Moreover, the used doping method is fast and straightforward and can be used to control the structure as well as the PL properties of molybdenum oxide nanomaterials.